PENGARUH RETURN ON ASSET, RETURN ON EQUITY, NET PROFIT MARGIN, DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Bayu Takaful (Program Studi Manajemen Fakultas Ekonomi UST, 2021)
This study aims to examine the effect of Return on Asset (ROA), Return On Equity (ROE), Net Profit Margin (NPM), and Earning Per Share (EPS)on Stock Price. Samples taken were 15 LQ45 companies listed on the Indonesia Stock Exchange in 2014-2018. Analysis techniques using purposive sampling techniques. The results of this study are that the Return On Asset (ROA) has a negative and not significant effect on stock price, Return On Equity (ROE) has a positive and significant effect on stock prices, Net Profit Margin (NPM) has a negative and significant effect on stock prices, Earning Per Share (EPS) has a positive and not significant effect on stock prices, and together Return On Asset (ROA), Return On Equity (ROE), Net Profit Margin (NPM), and Earning Per Share (EPS) have a significant effect on stock prices.